Pengaruh Karbon Aktif Sebagai Katalis pada Generator HHO terhadap Nyala Api - Supriadi, Supriadi; Ismail, Nova Risdiyanto; Soebiyakto, Gatot (PROTON, 2024)
This study was conducted with the aim of knowing the impact of the addition of activated carbon in the electrolysis process on the temperature and area of the fire color zone. This research uses an HHO generator with variations in the mixture of salt and activated carbon with a time of 5, 10, and 15 seconds. This research was conducted experimentally with a plate spacing of 1.5 mm and the highest temperature of 154.8⁰C in the salt mixture. The average area of the largest flame color zone is in the salt mixture of 33.75 mm2.